2016
DOI: 10.4172/2161-1165.1000272
|View full text |Cite
|
Sign up to set email alerts
|

Timely Initiation of Complementary Feeding and Associated Factors among Children Aged 6 to 12 Months in Addis Ababa Ethiopia, 2015

Abstract: Introduction: Appropriate nutrient intake and/or complementary feeding in quantity, bioavailability and timely in infancy period are essential for optimal growth and development. Initiation of safe and nutritionally adequate complementary foods at 6 month is crucial to achieve optimal growth, development and health. Exclusive breastfeeding) for the first six months of life is critical for the wellbeing of the infant. This study aim was to assess the prevalence of timely initiation of complementary feeding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Thus, children need breast milk plus additional (complementary) feeding to fill the lagging nutrients gap that is known for 45% of child deaths in low and middle-income countries 3 , 4 . Some studies defined timely complementary feeding as the food combined with breast milk within the 6–8 months after birth 5 7 . The United Nations Children’s Fund (UNICEF) informs that families have been challenged by economic, political, market, social, or cultural barriers to feed their children affordably and safely in every corner of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, children need breast milk plus additional (complementary) feeding to fill the lagging nutrients gap that is known for 45% of child deaths in low and middle-income countries 3 , 4 . Some studies defined timely complementary feeding as the food combined with breast milk within the 6–8 months after birth 5 7 . The United Nations Children’s Fund (UNICEF) informs that families have been challenged by economic, political, market, social, or cultural barriers to feed their children affordably and safely in every corner of the world.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Nigeria showed that orthodox maternity care, exclusive breastfeeding, and absence of the siblings were associated with the timely initiation of complementary feeding 20 . In Ethiopia, women's employment, husband education, birth preparedness, growth monitoring, knowledge of time to introduce complementary feeding, and parental support were some of the factors affecting the time to initiate complementary feeding among mothers 7,13,[21][22][23] . In another study, maternal education, complementary feeding counseling, and maternal knowledge also influenced the timing of initiating complementary feeding 15 .…”
mentioning
confidence: 99%
“…Failure to give a great attention to timely initiation of complementary feeding puts the children at risk for malnutrition. Malnutrition has been responsible, directly or indirectly 10.9 million deaths annually among children under five due to lack of timely initiation of complementary feeding [ 18 , 19 ]. Despite its serious socioeconomic and health impact on children and community, it is not well studied in Ethiopia specifically in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proportion of Ethiopian children starting complementary food within the appropriate age range (6-8 months) remains a problem, with a pooled national prevalence of 62.5%, which increases with women giving birth at health care institutions and lower among working women (Habtewold et al, 2019;Yeheyis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At 6 months of age, breast milk alone can no longer meet child nutritional requirements, and early and late introduction of solid food carries growth and development risks (WHO, 2008 ). However, the proportion of Ethiopian children starting complementary food within the appropriate age range (6–8 months) remains a problem, with a pooled national prevalence of 62.5%, which increases with women giving birth at health care institutions and lower among working women (Habtewold et al, 2019 ; Yeheyis et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%